2008
DOI: 10.1021/jf073123c
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antioxidant Activity of 4-Methylthio-3-butenyl Isothiocyanate from Raphanus sativus L. (Kaiware Daikon) Sprouts

Abstract: There is high current interest in the chemopreventive potential of Brassica vegetables (cruciferae), particularly due to their content in glucosinolates (GL), which upon myrosinase hydrolysis release the corresponding isythiocyanates (ITC). Some ITCs, such as sulforaphane (SFN) from broccoli ( Brassica oleacea italica), have been found to possess anticancer activity through induction of apoptosis in selected cell lines, as well as indirect antioxidant activity through induction of phase II detoxifying enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 42 publications
5
100
0
1
Order By: Relevance
“…*p<0.05 as compared to control (0 µM) were affected following exposure of the cells line to the glucosinolate (Figure 2). When myrosinase was added to the glucosinolate-containing incubations, the inductive this enzyme at pH 7.4 allows to its complete hydrolysis to produce the isothiocyanate (Papi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05 as compared to control (0 µM) were affected following exposure of the cells line to the glucosinolate (Figure 2). When myrosinase was added to the glucosinolate-containing incubations, the inductive this enzyme at pH 7.4 allows to its complete hydrolysis to produce the isothiocyanate (Papi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Alessio Papi reported that Sulforaphane (SFN) caused a complete growth inhibition at 50 μM, whereas MTBITC showed only 15 (±5)% inhibition. It showed MTBITC with limited toxicity to normal human T-lymphocytes (Papi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Karen-Ng et al, 2013;Zhu et al, 2013; MTBITC is a major phytochemical constituent of radish as well as other cruciferous vegetables with known chemopreventive properties. MTBITC has been shown to modulate the activity of phase II detoxification enzymes (Hanlon et al, 2007), suppress proliferation, and induce apoptosis in cancer cells (Papi et al, 2008), via pathways that have been suggested to be involved in anticarcinogenic processes. However, few studies have been carried out to ascertain the effects of MTBITC treatment in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) More recently, MTBI and its bioprecursor, 4-methylthio-3-butenyl glucosinolate (MTBG, 1), have been found to possess unique antioxidant and cytotoxic activities, boosting intense research interest in them. 3) Kosemura et al (1993) suggested that MTBI is released from MTBG via myrosinase (thioglucosidase) action (Fig. 1).…”
mentioning
confidence: 99%